Singing Sums: Investigating the Integration of Song Singing in the Teaching and Learning of Mathematics from Junior Infants to Second Class - Ní Dhaltúin, Clodagh (Marino Institute of Education, 2022)
This dissertation investigates the integration of song singing in the teaching and learning of mathematics from junior infants to second class. The researcher aims to provide critical insights into the perspectives and experiences of Irish primary teachers on using song singing in primary school and how song singing can be integrated into the teaching and learning of mathematics in the junior classes. At a time when the current Primary Mathematics Curriculum is being redeveloped, it is pertinent to address the opportunities for integration across the new curriculum. Through a comprehensive review of the literature, the researcher identifies key themes that relate to song singing, mathematics, and integration in the junior classes of primary school. By adopting a qualitative methodology, the researcher conducts semi structured interviews with a purposive sample of Irish primary teachers, to collect data that relates to the themes presented in the literature. The findings of this study indicate that song singing is used by teachers, both outside of and across the primary curriculum. A range of benefits in using it in the teaching and learning of mathematics in the junior classes also came from the data, such as song singing for memorisation, engagement, and relatedness to children’s lives. Some challenges also came from the data, such as a teacher’s lack of song singing confidence, a lack of readily available song singing and mathematical resources, and the pressure of having to complete the mathematics textbooks, which can inhibit opportunities for integrated and inclusive lessons. However, as recommended by the researcher, these challenges can be addressed through the development of Continuous Professional Development (CPD) courses and the development of readily available song singing and mathematical resources to support primary teachers in this opportunity for integration
Keywords: Music in mathematics education; Mathematics--Study and teaching; Education, Primary; Primary school teachers; Irish Primary Curriculum; Qualitative research; Semi-structured interviews; Continuous Professional Development; Song singing; Music in mathematics education; Mathematics--Study and teaching; Education, Primary; Primary school teachers; Irish Primary Curriculum; Qualitative research; Semi-structured interviews